Stability analysis of the tunnel face adjacent to longitudinal stratigraphic interface using the upper bound theorem - Jian Shi; Shilin Zhang; Binghe Zhang; Sen Teng; Mingkai Zhao (Alexandria Engineering Journal)
The secure condition of the tunnel face perpetually remains as a matter of substantial concern throughout the execution of tunnel-construction endeavors. Especially in composite formations, the presence of longitudinal stratigraphic interfaces makes it an exceptionally complicated issue. An improved segmented three-dimensional collapse mechanism was constructed to account for the effects of lithological mutations on the face instability characteristics of tunnels. Then, the critical support pressure was evaluated in the context of kinematic limit analysis and the nonlinear Hoek-Brown failure criterion. The validity of the proposed model was confirmed by comparison with numerical simulations and theoretical results from literature. The impact of the distance between the tunnel face and the stratigraphic interface (L), the tunnel diameter (d), and the Hoek-Brown parameters on the support pressure and collapse mode were analyzed further. The results indicate that the face stability is predominantly determined by the geological parameters of the fractured rock mass and exhibits a consistent decrement with the increase of both L and d. A decline in the geological strength index (GSI), material constant (mi) and uniaxial compressive strength (σci), or an escalation in the disturbance factor (D) of the fractured rock mass results in an increase in the critical support pressure and an expansion of the potential failure range.